2021
DOI: 10.1038/s41598-021-02049-w
|View full text |Cite
|
Sign up to set email alerts
|

Meta-QTLs and candidate genes for stripe rust resistance in wheat

Abstract: In bread wheat, meta-QTL analysis was conducted using 353 QTLs that were available from earlier studies. When projected onto a dense consensus map comprising 76,753 markers, only 184 QTLs with the required information, could be utilized leading to identification of 61 MQTLs spread over 18 of the 21 chromosomes (barring 5D, 6D and 7D). The range for mean R2 (PVE %) was 1.9% to 48.1%, and that of CI was 0.02 to 11.47 cM; these CIs also carried 37 Yr genes. Using these MQTLs, 385 candidate genes (CGs) were also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 74 publications
2
27
0
Order By: Relevance
“…Since most of the markers used in this study have already been mapped, the chromosome to which they were assigned is known. Physical QTL intervals for gene annotation were set according to the expected LD decay of 1 Mb on either side of the peak marker, i.e., 2 Mb interval in total ( Yu et al, 2020 ; Jan et al, 2021 ). Physical locations of peak markers were identified by anchoring these to the physical reference sequence IWGSC RefSeq v1.0 ( Appels et al, 2018 ) and QTL intervals were searched for corresponding v1.0 annotations using WheatMine search ( Alaux et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since most of the markers used in this study have already been mapped, the chromosome to which they were assigned is known. Physical QTL intervals for gene annotation were set according to the expected LD decay of 1 Mb on either side of the peak marker, i.e., 2 Mb interval in total ( Yu et al, 2020 ; Jan et al, 2021 ). Physical locations of peak markers were identified by anchoring these to the physical reference sequence IWGSC RefSeq v1.0 ( Appels et al, 2018 ) and QTL intervals were searched for corresponding v1.0 annotations using WheatMine search ( Alaux et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the present study identified at least 302 CGs ( Supplementary Table 3 ) encoding different proteins involving the following: ABC transporter type 1, trans membrane domain, AP2/ERF domain-containing proteins, basic-leucine zipper domain-containing proteins, calcium-dependent channel, cytochrome P450, glycoside hydrolase family domain-containing proteins, protein kinase, NAC transcription factor, NB-ARC domain, SANT/Myb domain, zinc finger domain containing proteins, etc. Recent findings suggest that these domains are important in R protein interactions as well as in other defense related proteins including pathogen effector proteins and in the activation of innate immunity signal transduction pathways ( Liu et al, 2007 ; Kumar et al, 2020 ; Jan I. et al, 2021 ). For instance, the rice Xa21 gene for bacterial blight resistance ( Xanthomonas ) and the tomato Cf genes for resistance to the fungal pathogen Cladosporium fulvum belong to the extracellular LRR class of R genes ( Ellis et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-QTL (MQTL) analysis assembles information from multiple studies and refines QTL locations by narrowing down the confidence intervals obtained from individual studies and correlating them with each other ( Goffinet and Gerber, 2000 ). MQTL analysis involving known QTLs for any particular trait has been conducted in several crops for various traits, including yield-related traits ( Tyagi et al, 2015 ; Saini et al, 2022c ), stripe rust resistance ( Jan I. et al, 2021 ), multiple disease resistance ( Pal et al, 2022 ; Saini et al, 2022a ), thermo-tolerance ( Kumar et al, 2021 ), salinity stress ( Pal et al, 2021 ), multiple abiotic stress tolerance ( Tanin et al, 2022 ) in wheat, nitrogen use efficiency ( Sandhu et al, 2021 ), grain size and African gall midge resistance ( Yao et al, 2016 ; Daware et al, 2017 ) in rice and protein and oil content in soybean ( Van and McHale, 2017 ). However, only a very few reports are available for MQTL analysis in this important legume crop for different traits including seed Fe and Zn concentrations ( Izquierdo et al, 2018 ) and white mold resistance ( Vasconcellos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous additional QTLs for APR to Pst have been detected since 2017 [30][31][32][33]66]. We aligned the APR GWAS results with those QTLs reported in the QTL reviews of Wang and Chen (2017) and Jan et al (2021) (Figure S9) [5,6]. We found that 3 of the 13 APR loci do not align with any previously identified QTL and, therefore, may be novel (Table 3).…”
Section: Adult Plant Resistancementioning
confidence: 57%
“…Currently, there are 83 designated genes and 67 provisionally designated genes for stripe rust resistance. Moreover, 61 quantitative trait loci (QTLs) have also been described for stripe rust resistance in wheat or its wild relatives [4][5][6]. However, many of the known resistance genes are no longer effective, at least in some parts of the world, due to the emergence of Pst races that are virulent on the resistance genes used for developing widely grown commercial cultivars [3].…”
Section: Introductionmentioning
confidence: 99%